Development of a control system for laser doppler imaging scanning technique using labview - Mukhtar, S.R.; Shanmugam, S.A.; Ibrahim, F. (2005)
To monitor a small region of skin tissue for blood perfusion mapping construction, a Y-Z scanning control system using X-Y mechanism was developed. This control system utilizes the combination of a Stepper Motor and a DC Motor. A GCP (Graphical Coded Programming) of LabVIEW is used to compute the system driver controller via DAQ (Data Acquisition) card of PCI E-series. The results presented are based on experimental observation. Results show that the design is capable of performing the Y-Z scanning pattern up to 25 mm Ã 25 mm AOI (Area of Interest). Â© 2005 IEEE.